Changes in body composition revealed by bioelectrical impedance analysis reflect strength and motor performance in myotonic dystrophy type 2 - Frezza, Erica; Merra, Giuseppe; Greco, Giulia; Goglia, Mariangela; Seraceno, Silvia; Boffa, Laura; Mercuri, Nicola B.; De Lorenzo, Antonino; Massa, Roberto (Frontiers in Neurology, 2024)
IntroductionIn myotonic dystrophy type 2 (DM2), metabolic dysfunctions are frequent. Therefore, measurement of muscle mass and body composition by non-invasive methods could help in evaluating disease severity and progression. The aim of our study was to investigate, by means of bioelectrical impedance analysis (BIA), whether DM2 patients have an alteration in their body composition and if this finding correlates with strength and motor performances.MethodsWe obtained anthropometric measures, nutritional data, BIA and blood tests in 18 DM2 patients and correlated them with motor function tests.ResultsThe 33% of male and 22% of female patients had BMI values compatible with severe obesity, whereas 44% of males and 33% of females had a metabolic syndrome. Considering BIA parameters, phase angle was under normal values in 56% of males and 89% of females. This may be regarded as a marker of deranged cell membrane function. Motor tests showed a fair to strong direct correlation with several BIA parameters.ConclusionThese data suggest that BIA findings may be faithful markers of the degree of muscle wasting and impairment in DM2. The different degree of BIA alterations between genders indicate that body composition undergoes sex-related modifications in this disease. The potential of this technique to capture changes in a slowly progressive disorder such as DM2 should be tested in longitudinal studies.